The effects of cancer drugs and copper complexes on pancreatic cancer haem oxygenase-1 and cell survival - Jhetam, Zakeeya (University of the Witwatersrand, Johannesburg, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic malignancy. PDAC is one of the deadliest cancers, with a 5 year survival rate of only 3.2 % when diagnosed at an advanced stage. Approximately 75-80 % of PDAC cases are diagnosed at a late/inoperable stage where palliative chemotherapy is the only treatment option available. Current treatment options are met with numerous challenges. Despite the advances and success in targeted therapy and immune checkpoint blockade in various solid tumours, PDAC is unresponsive to these treatments. The stress-response protein, HMOX1, has been implicated in treatment failure of chemotherapy in numerous cancer-types. There is a need for novel therapeutic approaches in the treatment of PDAC and the reasons for treatment failure of chemotherapy for pancreatic cancer cells requires urgent attention. Copper complexes as anticancer agents have shown promising cytotoxicity against numerous cancers, and appear to cause cell death by inducing apoptosis. The ligands to which copper are complexed play a major role in the specificity and mode of cell death of the complexes. The ligands that were evaluated in this study had previously shown anti-cancer activity, and allow the binding of the complexes to DNA. This study evaluated three different classes of copper complexes for their anti-cancer activity on AsPC-1 and MIA PaCa-2 pancreatic cancer cells. A copper- phenanthroline-theophylline complex (AD3), a copper 8-aminoquinolone naphthyl complex (OM), and two copper isoindoline complexes (L1Cu and L6Cu) were cytotoxically active in both the AsPC-1 and MIA PaCa-2 cell lines. The complexes had clinically relevant IC50 values of below 5 μM and were significantly more active than the positive control, doxorubicin. Preliminary investigations on the effect of the copper complexes on the morphology of the cells indicated the absence of necrotic cell death, while features of apoptosis, such as membrane blebbing and chromatin condensation were observed. The copper complexes caused statistically significant formation of reactive oxygen species (ROS), in both cell lines. The copper complexes caused the binding of annexin-V in both cell lines and provided evidence for apoptosis. Apoptotic cell death was confirmed by the activation of caspase-3/7, with copper complexes causing between 16 % and 67 % caspase-3/7 activation in AsPC-1 cells while >88% of MIA PaCa-2 treated cells had active caspase-3/7. The loss of mitochondrial membrane potential was seen in 100 % of treated cells in both cell lines with the activation of caspase-9 confirming activation of the intrinsic apoptotic pathway. v The copper complexes increased the expression of HMOX1 in both cell lines, as seen in immunofluorescence and western blot studies. AD3 was the strongest inducer of HMOX1 whilst L1Cu caused the smallest increase in HMOX1 expression. The inhibition of HMOX1 by a small-molecule inhibitor, OB24 HCl, significantly decreased the IC50 values of the copper complexes, indicating that HMOX1-inhibition sensitized the cells to the cytotoxic effect of the copper complexes. At the concentration used, OB24 HCl had no effect on cell viability. The data suggested that HMOX1-inhibition may be a viable therapeutic consideration in PDAC. Taken together, the data from this study supports the further pre-clinical investigation of copper complexes as cancer treatments together with an in depth investigation on HMOX1.
A research report submitted in fulfillment of the requirements for the Master of Sciences in Medicine, in the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Pancreatic cancer; copper complexes; intrinsic apoptosis; haem oxygenase-1; SDG-3: Good health and well-being